Pressure compression of the access tract for tubeless percutaneous nephrolithotomy - Shun-Kai Chang (Urological Science, 2019)
Objective: To obtain adequate hemostasis, we compressed the access tract at the end of operation for tubeless percutaneous nephrolithotomy (PCNL). The clinical results of 216 consecutive patients were evaluated by retrospective chart review. Materials and Methods: After stone extraction, an 8F Foley catheter was inserted into the renal pelvis and was then inflated and gently retracted. The working sheath was withdrawn to the renal capsule, the renal access tract was packed with oxidized regenerated cellulose (SurgicelTM) strips, and the tract was compressed with smaller dilators through the working sheath for 5 min. Results: Of the 216 patients, 139 were male and 77 were female. The mean age was 56.0 ± 11.7 years. The stone characteristics were renal stones in 146 patients, ureteral stones in 47 patients, and kidney with ureteral stones in 23 patients. The average stone size was 3.6 ± 2.1 cm, and the average operation time was 80.5 ± 30.1 min. The target stones were all removed in each patient and the overall postoperative stone-free rate was 73.6%. The postoperative blood transfusion rate was 1.4% (three patients). Postoperative fever was noted in 23 patients (10.6%) and sepsis was noted in three patients (1.4%). The average postoperative hospital stay was 3.2 ± 1.4 days. Conclusion: Our results suggest that pressure compression may be an alternative method to minimize hemorrhagic complications during tubeless PCNL.